2008
DOI: 10.1111/j.1553-2712.2007.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Has Direct Toxicity on the Myocardium Distinct from Effects of Hypoxia in an Ex Vivo Rat Heart Model

Abstract: Objectives: Carbon monoxide (CO) toxicity causes significant central nervous system and cardiac injury. Although the neurological damage caused by CO toxicity is extensively described, the mechanisms underlying myocardial insult are unclear. The authors used an externally perfused isolated rat heart model to examine the effects of a physiological saline solution (Krebs Henseleit HEPES, KHH) aerated with CO on cardiac function.Methods: Fifteen rats were equally divided into three groups: the control group (KHH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The classical hypothesis is that the binding of CO to intracellular myoglobin in the myocardium impairs oxygen delivery to the mitochondria, and that subsequent energy disorders lead to cardiac contractile decrease [58][59][60][61][62]. Carbon monoxide is also directly toxic for mitochondria, with impairment of mitochondrial respiratory chain at the cytochrome c oxidase level, decrease of glutathione concentrations and of ATP generation [63][64][65]. Finally, a catecholamine surge is also likely involved, mainly for the takotsubo pattern [55].…”
Section: Carbon Monoxidementioning
confidence: 99%
“…The classical hypothesis is that the binding of CO to intracellular myoglobin in the myocardium impairs oxygen delivery to the mitochondria, and that subsequent energy disorders lead to cardiac contractile decrease [58][59][60][61][62]. Carbon monoxide is also directly toxic for mitochondria, with impairment of mitochondrial respiratory chain at the cytochrome c oxidase level, decrease of glutathione concentrations and of ATP generation [63][64][65]. Finally, a catecholamine surge is also likely involved, mainly for the takotsubo pattern [55].…”
Section: Carbon Monoxidementioning
confidence: 99%
“…CO has a significant affinity for all iron or copper containing sites and competes with oxygen at these active sites. The affinity of hemoglobin for CO is 250 times higher than that for oxygen , the result is the formation of carboxy hemoglobin (CO-Hb) which is a molecule incapable of carrying O2 to tissue sites resulting in tissue hypoxia (Suner and Jay, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in this study, MS decreased pathological insults induced by CO. Also, histopathological results showed that MS-treated rats exert reduced necrosis rates in cardiomyocytes as compared to the control group. Cardiac ischemia is the hallmark of cardiotoxicity of CO poisoning ( 17 ). The main mechanism underlying CO poisoning is binding of CO to hemoglobin, resulting in a left-ward shift of oxyhemoglobin curve and tissue hypoxia ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac ischemia is the hallmark of cardiotoxicity of CO poisoning ( 17 ). The main mechanism underlying CO poisoning is binding of CO to hemoglobin, resulting in a left-ward shift of oxyhemoglobin curve and tissue hypoxia ( 17 ). Hemoglobin affinity to CO is about 200-250 times higher than its affinity to O2 ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation